1999
DOI: 10.1021/ac990714w
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Dispersion of a Neutral Nonreacting Solute in Electroosmotic Flow

Abstract: Analytical methods are employed to determine the axial dispersion of a neutral nonreacting solute in an incompressible electroosmotic flow. In contrast to previous approaches, the dispersion is obtained here by solving the time-dependent diffusion−advection equation in transformed spatial and temporal coordinates to obtain the two-dimensional late-time concentration field. The coefficient of dispersion arises as a separation eigenvalue, and its value is obtained as a necessary condition for satisfying all of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 4 publications
5
102
0
Order By: Relevance
“…Velocity gradients across the channel cross section are central to dispersion, as they induce a shearing action ͑Taylor, 1953͒. Convective dispersion in microfluidic channels has been reviewed by Squires and Quake ͑2005͒; it is different for pressuredriven and electro-osmotic flow due to their parabolic and plug flow profiles, respectively ͑Griffiths and Nilson, 1999Stein et al, 2006͒. In nanochannels, the previously mentioned electrokinetic effects increase the dispersion rate of counterions and decrease the rate of coions ͑De Leebeeck and Sinton, 2006͒. These authors also showed that the radially limited diffusion of ions by electromigration in response to the wall charge increases the dispersion of all ions relative to neutral species.…”
Section: ͑29͒mentioning
confidence: 99%
“…Velocity gradients across the channel cross section are central to dispersion, as they induce a shearing action ͑Taylor, 1953͒. Convective dispersion in microfluidic channels has been reviewed by Squires and Quake ͑2005͒; it is different for pressuredriven and electro-osmotic flow due to their parabolic and plug flow profiles, respectively ͑Griffiths and Nilson, 1999Stein et al, 2006͒. In nanochannels, the previously mentioned electrokinetic effects increase the dispersion rate of counterions and decrease the rate of coions ͑De Leebeeck and Sinton, 2006͒. These authors also showed that the radially limited diffusion of ions by electromigration in response to the wall charge increases the dispersion of all ions relative to neutral species.…”
Section: ͑29͒mentioning
confidence: 99%
“…However, it provides no direct knowledge of either the mean migration velocity or the effective dispersion coefficient of solutes, where the former determines whether solutes can be separated while the latter governs the resolution [21]. As the hydrodynamic dispersion is proportional to the square of the channel transverse dimension in both pressure- [22,23] and electric field-driven flows [24,25], it becomes trivial in nanochannels even though the variation of fluid velocity across the channel may become very significant [6][7][8][9][11][12][13][14][15]. Moreover, such dispersion has no direct influence on the mean migration velocity of solutes.…”
Section: Solute Transport In Nanofluidic Channelsmentioning
confidence: 99%
“…Some of them addressed pressure-driven flow, whereas in some studies electrically driven flow and combined pressure-electrically-driven flow were considered. Assuming low electric potentials at the wall/solution interface, Datta (1990), McEldoon and Datta (1992), and Griffiths and Nilson (1999) evaluated the electroosmotic dispersion coefficient for the circular and plane parallel channels. For higher wall potentials, the electroosmotic dispersion was addressed by Lisin (1992, 1993), Gas et al (1995), Griffiths and Nilson (2000), and Zholkovskij et al (2003).…”
Section: Introductionmentioning
confidence: 99%